2019
DOI: 10.1136/jmedgenet-2018-105513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diagnosis of subfertility: the impact of meiosis and maternal effects

Abstract: During reproductive age, approximately one in seven couples are confronted with fertility problems. While the aetiology is diverse, including infections, metabolic diseases, hormonal imbalances and iatrogenic effects, it is becoming increasingly clear that genetic factors have a significant contribution. Due to the complex nature of infertility that often hints at a multifactorial cause, the search for potentially causal gene mutations in idiopathic infertile couples has remained difficult. Idiopathic infertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 171 publications
0
10
0
Order By: Relevance
“…Besides sister cohesion, many other factors including the states of kinetochore, spindle, checkpoint, environment, and recurrence of DNA damage also have important contributions to chromosome mis-segregation and thus maternal age effect. 134 135 136 137 138 139 140 …”
Section: Co Patterns and The High Frequency Of Human Aneuploidiesmentioning
confidence: 99%
“…Besides sister cohesion, many other factors including the states of kinetochore, spindle, checkpoint, environment, and recurrence of DNA damage also have important contributions to chromosome mis-segregation and thus maternal age effect. 134 135 136 137 138 139 140 …”
Section: Co Patterns and The High Frequency Of Human Aneuploidiesmentioning
confidence: 99%
“…18,19 Genetic Causes of Poor Oocyte Quality in Young Women with Unexplained Infertility Recent genetic and cell-based studies have identified severe defects in diverse facets of oocyte development that impact oocyte and embryo quality. 30 Many such patients have no detectable abnormalities using conventional testing of sperm, tubes, and ovulation and are therefore categorized as unexplained infertility.…”
Section: Poor Oocyte Quality Independent Of Aging Effectsmentioning
confidence: 99%
“…The patients for whom this type of genetic interrogation might be appropriate could be identified during IVF treatment because of unusually low oocyte maturation, extremely low fertilization, or very poor embryo development. 30 Identifying patients with mutations would help tailor treatment, thereby avoiding interventions unlikely to be beneficial such as those targeted at age-induced oocyte quality decline and would also expedite the transition to more suitable options such as use of donor oocytes.…”
Section: Prospects and Challenges For Diagnosing And Improving Poor Omentioning
confidence: 99%
“…The alteration of the meiotic program is at the basis of an important number of fertility problems ( Handel and Schimenti, 2010 ; Hann et al, 2011 ; Geisinger and Benavente, 2016 ; Gheldof et al, 2019 ; Veitia, 2020 ) and other pathologies (e.g., Tsui and Crismani, 2019 ), including cancer ( Feichtinger and McFarlane, 2019 ). Therefore, the need to improve the knowledge on the molecular groundwork of meiosis in mammals is obvious.…”
Section: Introductionmentioning
confidence: 99%